Implementasi Skema Meaningful Sharing pada Kriptografi Visual Berwarna untuk Digital Safe Deposit Box - Willy Sudiarto Raharjo; Danny Aguswahyudi (Ultimatics : Jurnal Teknik Informatika, 2016)
Conventional key being used in safe deposit box is a physical key that is easily duplicated, stolen and abused by irresponsible parties. This research proposed a model that substitutes the conventional key with a digital shared secret with the use of visual cryptography scheme. Visual cryptography hide the secret image into two or more images which are called share images that will not reveal anything about secret image if they were separated. The secret image can be recovered simply by stacking the shared images together without any complex computation. In this research, we propose a digital safe deposit box built using a color visual cryptography scheme. The proposed system will generate secret images containing passphrase that will be hidden in two shared images. The shared images are used for substituting the traditional key. We found 93% of the stacked image are visually readable by human eye and Arial-Courier font combination are more readable compared to Times New Roman-Calibri with 95% compared to 92% during human visual verification process. Index Terms— visual cryptography, secret sharing